Earlier emergence of winter-spring maximum streamflow across Poland, 1981–2020 - Somorowska, Urszula (Acta Geographica Lodziensia, 2024)
Rivers in Poland present nival, nivo-pluvial and pluvio-nival water regimes with considerable peak flows occurring at the winter spring turn in March, April or May. As climate warming occurs, the snow fraction of precipitation may change, and the atmospheric thaws might occur earlier, causing changes in the streamflow patterns. In this study, the date of the maximum streamflow occurrence at the winter-spring turn was analyzed during the period from 1981–2020 to detect possible changes in the river regime. Daily streamflow data from 102 river gauging stations across Poland were filtered with the moving average shifting horizon (MASH) method to filter out the short-term variability observed at daily and inter-annual scales. Then, the modified Mann-Kendall statistical test and the Theil-Sen slope were employed to assess the trend presence and magnitude of the observed date of the peak flow occurrence. A clear shift in the timing of the springtime maximum streamflow towards earlier in the year was revealed in many rivers across the country. An acceleration of the streamflow maximum was observed in 87 out of 102 analyzed rivers, ranging from –8 to –108 days. A 9-day delay was detected at one mountainous site. The other 14 rivers did not show a statistically significant shift.